Factors associated with parental mediation of children’s gadget use among parents of elementary school students - Sarini Sarini; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Okti Rahayu Asih; Dewi Rubi Fitriyani; Dayana Noprida (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The rapid growth of digital technology has transformed children's learning and communication patterns while simultaneously increasing their exposure to digital risks, including excessive gadget use, cyberbullying, inappropriate online content, and internet addiction. Parents play a fundamental role in protecting children from these risks through effective parental mediation strategies. The implementation of such strategies may be influenced by several factors, including parental digital literacy, parenting style, educational level, age, and socioeconomic status. However, evidence regarding the determinants of parental mediation strategies among parents of elementary school children in Indonesia remains limited. Purpose: To identify factors associated with parental mediation strategies for managing children's gadget use. Method: A quantitative analytical study with a cross-sectional design was conducted among 60 parents of first- and second-grade students at SDIT Sehati Bina Insani, Karawang. Total sampling was employed to recruit all eligible participants. Data were collected using validated questionnaires assessing respondents' characteristics, parental digital literacy, parenting style, and parental mediation strategies. Descriptive statistics were used to summarize respondent characteristics, while Chi-square and Fisher's Exact tests were performed to examine associations between independent variables and parental mediation strategies. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to estimate the strength of associations, with statistical significance set at p < 0.05. Results: Parenting style and parental digital literacy were significantly associated with parental mediation strategies (p = 0.001 and p < 0.001, respectively). In contrast, parental age (p = 0.962), educational level (p = 0.418), and family income (p = 0.238) were not significantly associated with parental mediation strategies. Parental digital literacy was identified as the strongest predictor of effective parental mediation (OR = 18.21; 95% CI: 4.16–79.69), followed by democratic parenting style (OR = 6.31; 95% CI: 2.11–18.85). Conclusion: Parental digital literacy and parenting style are significant determinants of effective parental mediation strategies for children's gadget use. Parents with higher digital literacy and democratic parenting practices are more likely to implement effective mediation strategies. Strengthening parents' digital literacy through school- and community-based educational programs may enhance children's safe and responsible use of digital technology.